The Patriotism Values in Main Characters in The Red Cliff Film By John Woo: Sociology of Literature Review 吴宇森对 《赤壁》电影中主角爱国主义价值观：文学社会分析 - Sania Widyastira JP; Intan Erwani (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2023)
This research discussed the values of the main character in the Chinese movie